Manajemen Pengembangan Kompetensi Entrepreneurship Santri: Studi Kasus Pada Pondok Pesantren Nurul Islam II Jember - Zaini, Mohammad (CV. Creative Tugu Pena, 2022)
Islamic Boarding School education based on theological values ??to increase the values ??of piety that adheres to the national education system which at the Ministry of National Education and religion adopted the Ministry of Religion. Empirical evidence that national education has a great influence on the implementation of both general and religious education. The purpose of this study is to describe the activities and concrete results of Islamic boarding school education on the entrepreneurial attitudes and skills of students. This study aims to examine and describe problems related to: (1) Islamic boarding school education strategies to develop students' entrepreneurial values ??and attitudes; (2) How pesantren education facilitates santri into education based on mastery of religious values ??and entrepreneurial spirit; (3) The challenges faced by the two Islamic boarding schools in developing the values ??and attitudes of students in Islamic boarding schools for entrepreneurship. In this study, researchers collected qualitative data, related to the management of Islamic boarding schools to build students' attitudes and skills for entrepreneurship. Students' attitudes and skills in entrepreneurship include: discipline, independence, fairness based on results, risk taking, leadership and future orientation. The idea came because Kyai saw that not all alumni would be accepted as company employees. Therefore, alternative steps are needed by presenting young entrepreneurs with Islamic perspectives. In this case, the implications for the development of entrepreneurship in students will slowly run. The cause has many challenges in developing and becoming entrepreneurial students.